2019
DOI: 10.32662/gomares.v2i2.766
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Locus Of Control Terhadap Organization Citizenship Behavior Pegawai Pada Perusahaan Daerah Air Minum Kota Gorontalo

Abstract: Abstrac Pengaruh Locus Of Control Terhadap Organizational Citizenship Behavior Pegawai  pada Perusahaan Daerah Air Minum Kota  GorontaloTujuan penelitian ini adalah untuk mengetahui dan menganalisis Pengaruh Locus Of Control Terhadap Organizational Citizenship Behavior Pegawai  Penelitian ini menggunakan sampel sebanyak 63 responden, kuesioner dijadikan sebagai alat pengumpul data utama dan data dianalisis dengan menggunakan alat path analysisBerdasarkan hasil penelitian ini bahwa bahwa Locus Of Control yang I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…This demonstrated that employees with stronger self-control have higher OCB, leading to a more responsible attitude and a high level of initiative at work, where people select teamwork to complete tasks. This finding was congruent with previous research (Piola et al, 2019;Tistianingtyas & Parwoto, 2021;(Gheorghe, 2019;Suriyana, Nandan Limakrisna, & Andri Wijaya, 2020;Hsia & Tseng, 2015;Hakim, Putrawan, & Yufiarti, 2019;Pavalache-Ilie, 2014;Septiawati, 2019), which discovered that locus of control influences OCB positively.…”
Section: Path Analysis Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This demonstrated that employees with stronger self-control have higher OCB, leading to a more responsible attitude and a high level of initiative at work, where people select teamwork to complete tasks. This finding was congruent with previous research (Piola et al, 2019;Tistianingtyas & Parwoto, 2021;(Gheorghe, 2019;Suriyana, Nandan Limakrisna, & Andri Wijaya, 2020;Hsia & Tseng, 2015;Hakim, Putrawan, & Yufiarti, 2019;Pavalache-Ilie, 2014;Septiawati, 2019), which discovered that locus of control influences OCB positively.…”
Section: Path Analysis Resultssupporting
confidence: 91%
“…Employees who operate in environments with high levels of internal control will be more proactive in attaining goals, accountable for fostering an organizational learning culture, helpful to coworkers, more disciplined, and more perceptive to environmental cues. The results of Piola, Poppy, & Rahmisyari (2019) and Septiawati (2019) showed that locus of control had a positive effect on OCB, hence, the following hypothesis was proposed: H3: Locus of Control affects Organization Citizenship Behavior Employees' job satisfaction can be detected during work and in other aspects, such as communication with colleagues and supervisors, as well as compliance with regulations and in the work environment. Job satisfaction is the pleasant or unpleasant emotional state of employees in relation to their job.…”
Section: Introductionmentioning
confidence: 99%
“…Karyawan menggunakan sistem informasi untuk mengubah solusi dan proses kerja, serta memecahkan masalah berdasarkan rasa tanggung jawab. Piola et al (2019) Perilaku OCB merupakan perilaku yang ada dalam ajaran Islam didalam Al-Qur'an disebutkan bahwa seluruh umat Islam saling tolong menolong dalam berbuat kebaikan dan bertaqwa kepada Allah dan melarang umat Nya saling tolong menolong dalam dosa dan pelanggan (Al Maidah:2). Seperti yang diungkapkan oleh Kamil (2014), OCB dalam perspektif Islam merupakan tindakan sukarela dari individu yang sesuai dengan Syariah Islam dan hanya mengharapkan falah atau ridha Allah.…”
Section: A Pendahuluanunclassified
“…Menurut Fauzy & Luterlean (2020), baik Internal Locus of Control (ILOC) maupun Perceived Organizational Support (POS), secara simultan atau parsial memiliki pengaruh yang signifikan terhadap OCB. Sama halnya dengan Piola et al (2019), hasil penelitian ini menunjukkan bahwa ILoC dan ELoC secara simultan berpengaruh positif dan signifikan terhadap OCB pada pekerja PDAM, selebihnya ditentukan oleh faktor lain yang tidak diteliti meningkat. Dalam penelitian Khairunniswah & Mariatin (2015), hasil analisis statistik menggunakan regresi linier sederhana menunjukkan adanya pengaruh LoC menggunakan OCB pada staf PTPN IV di Unit Ajam.…”
Section: Pengaruh Locus Of Control Terhadap Organizational Citizenshi...unclassified
See 1 more Smart Citation